2019
DOI: 10.3389/fnins.2019.01022
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of mTOR Signaling Restricts Cell Proliferation in the Floor Plate

Abstract: The neural tube is composed of a number of neural progenitors and postmitotic neurons distributed in a quantitatively and spatially precise manner. The floor plate, located in the ventral-most region of the neural tube, has a lot of unique characteristics, including a low cell proliferation rate. The mechanisms by which this region-specific proliferation rate is regulated remain elusive. Here we show that the activity of the mTOR signaling pathway, which regulates the proliferation of the neural progenitor cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Importantly, we showed that glucose injections at 24 hpf rescued ~70% of E– embryos [ 11 ], providing a clue that earlier intervention may alter transcriptional responses and fully rescue E– animals through remediation of glycolysis. Importantly, vertebrate neurogenesis formation requires mTOR signaling [ 41 , 42 ] and mTOR is expressed in the zebrafish trunk and brain at 24 hpf [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we showed that glucose injections at 24 hpf rescued ~70% of E– embryos [ 11 ], providing a clue that earlier intervention may alter transcriptional responses and fully rescue E– animals through remediation of glycolysis. Importantly, vertebrate neurogenesis formation requires mTOR signaling [ 41 , 42 ] and mTOR is expressed in the zebrafish trunk and brain at 24 hpf [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For tissue analyses, the harvested embryos were fixed with 4% paraformaldehyde for 90 min, and were replaced with 15% (w/v) sucrose overnight with rotating incubation. These embryos were In situ hybridisation and TUNEL assays were performed as previously described [6,38,39].…”
Section: Manipulations and Histological Analyses On Chick Embryosmentioning
confidence: 99%
“…These embryos were embedded in OCT compound (Sakura) and cryosectioned to a thickness of 12 µm using a Polar cryostat (Sakura Finetek). The following antibodies were used in this study: Sox2 (rabbit; Millipore, #5603), In situ hybridisation and TUNEL assays were performed as previously described [6,38,39].…”
Section: Manipulations and Histological Analyses On Chick Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…SSC1: 159538854 was found to be an intron variant of the Ring finger protein 152 ( RNF152 ) gene, which has been identified as a negative regulation factor of mTOR signaling (Deng et al . 2015; Kadoya & Sasai 2019). The mTOR pathway is involved in cell metabolism, survival and proliferation by regulating anabolic processes, including protein, lipid and nucleotide synthesis (Gangloff et al .…”
Section: Figurementioning
confidence: 99%